Last interglacial sea levels and regional tectonics from fossil coral reefs in the northeast Gulf of Aqaba. (1st July 2018) - Bar, N.; Agnon, A.; Yehudai, M.; Lazar, B.; Shaked, Y.; Stein, M.
Abstract: Elevated reef terraces in the northeast Gulf of Aqaba (GOA) constrain the history of tectonic uplift and local relative sea level changes during the last interglacial period. These relative sea level changes were inferred from measured elevations coupled with U-Th ages of aragonite precipitation and recrystallization to calcite. All studied reef terraces were formed, and the corals comprising them were recrystallized from aragonite to calcite, when sea-level was at or close to its stable MIS5e elevation a few meters above the modern GOA level. The terraces comprise fringing reefs, some with clear reef structure consisting of a reef flat and a shallow back lagoon accurately marking sea levels at low tide. Terrace R3 probably formed at the earlier stage of MIS5e at ∼130–132 ka and recrystallized to calcite at 124 ± 8 ka. Terrace R2, comprising a wide and developed reef flat, formed during the stable sea-level of peak MIS5e at ∼129–121 ka and was recrystallized to calcite at 104 ± 6 ka. Terrace R1 formed during a short still-stand at 117 ± 3 ka. The recrystallization age of Terrace R2 implies that at around 104 ± 6 ka (MIS5c) sea-level was close to its MIS5e elevation. The elevation and ages of the reef flats indicate a slow average uplift, 0.13 ± 0.05 m/kyr, similar to rates inferred for other last interglacial reef terraces along GOA and the Red Sea. This suggests an overall long-term slow uplift of the Arabian lithosphere at the flanks of the Dead Sea Transform during the late Quaternary. Highlights: Slow (between ∼0.09 and ∼0.14 m/kyr) tectonic uplift rate at NE Gulf of Aqaba Since Last Interglacial. Elevated fossil coral reefs represent sea level variation during MIS5e. Wide and developed fringing reefs dominated the Aqaba shores at ∼ 129–121 ka. Possibly early MIS5e sea-level rise at the Gulf of Aqaba at ∼ 132–130 ka. Evidence that sea level was close to MIS5e elevation at ∼ 104 ka.